2017
DOI: 10.1515/corrrev-2017-0056
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel surface treatments for corrosion protection of aluminum: self-repairing coatings

Abstract: Two types of self-repairing coatings for the protection of Al and its alloys are reviewed: (1) organic coatings with capsules containing repairing agent and (2) porous anodic oxide films with inhibitor solution stored in the pores of the oxide film. First, polyurethane microcapsules containing liquid surface-repairing agents were synthesized and polyurethane coating with the capsules was painted on Al alloy specimens. After mechanical damage to the coating, self-repairing occurred by the reaction of water vapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Various materials have been used as capsules shells encapsulating healing agents, such as urea-formaldehyde [10][11][12][13], poly(urea-formaldehyde) [14][15][16], melamine(urea-formaldehyde) [17,18], polyurethane (PU) [19,20] and epoxy resins [21,22] embedded in polymeric matrixes. Recently, the use of natural polymers receives considerable attention, especially because of their environmentally friendly character.…”
Section: Introductionmentioning
confidence: 99%
“…Various materials have been used as capsules shells encapsulating healing agents, such as urea-formaldehyde [10][11][12][13], poly(urea-formaldehyde) [14][15][16], melamine(urea-formaldehyde) [17,18], polyurethane (PU) [19,20] and epoxy resins [21,22] embedded in polymeric matrixes. Recently, the use of natural polymers receives considerable attention, especially because of their environmentally friendly character.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of this study recently developed self-healing polyurethane coatings with micro-capsules containing healing agents. The healing mechanism is similar to that described above [18,19]. In this case, the capsules consist of a polyurethane shell and a diisocyanate core [20,21].…”
Section: Introductionmentioning
confidence: 71%
“…This is discussed in Section 4.1. In previous studies, the authors of this paper found that a Cu 2+ /Cl − solution is significantly useful for detecting imperfections in oxide films on Al alloys [18,19,22,23]. Cu 2+ and Cl − ions synergistically enhance the local corrosion of Al alloys through imperfections.…”
Section: Corrosion Behavior Of Self-healing Coating During Immersion ...mentioning
confidence: 80%